Дослідження баластного щебеню при перевезенні мінеральних добрив залізничним транспортом - Трикоз, Людмила Вікторівна; Багіянц, Ірина Вікторівна (НТУ "ХПІ", 2015)
У статті розглянуто вплив ступеня забрудненості баластного щебеню мінеральними добривами на величину його питомої електричної провідності. Встановлено, що ця величина може змінюватися в залежності від виду покриття на зернинах щебеню та від виду мінеральних добрив, що перевозяться залізницею. Таке покриття може бути запропоновано для обробки чистого щебеню перед його укладанням у колію під час ремонтів для продовження термінів експлуатації баластного шару, попередження адгезійного забруднення та ліквідації випадків помилкової зайнятості рейкових кіл.

The article deals with influence of contamination of the ballast bed from mineral fertilizers on its specific electric conductivity. Electric conductivity has been determined for both clean and contaminated ballast. The electric conductivity of treated broken stone has been defined by the following method: the samples have been saturated with distilled water in prescribed proportion and mixed thoroughly until saturated solution has been obtained. The saturation has been defined by constant measurements of its electric conductivity in a measuring tank until the electric conductivity of the solution stabilizes. The constant electric conductivity of the solution testifies that the solution is saturated.
The research of electrical conductivity of ballast breakstone during transportation mineral fertilizers railway transport
Keywords: рейкове коло; затримки по'іздів; забрудненість; track circuit; delays trains